"I Was Very Impressed": Responses of Surprise to Students of Color Engaged in Youth Participatory Action Research. (November 2019) - Bertrand, Melanie
This article explores decision makers' responses of surprise or amazement to Students of Color engaged in youth participatory action research (YPAR). To address this topic, I draw upon data collected from a yearlong qualitative study of a YPAR group, applying the theoretical aspects of critical discourse analysis. The findings indicate that the decision makers in the sample expressed surprise at three aspects of YPAR: the students' (a) capacity as researchers, (b) professionalism, and (c) motivation. These responses—termed "the discourse of surprise"—may have constrained the transformative potential of the students' research.